Programming Fundamentals - A Modular Structured Approach using C++ - Busbee, Kenneth Leroy; Open Textbook Library (Open Textbook Library, 2013)
Programming Fundamentals - A Modular Structured Approach using C++ is written by Kenneth Leroy Busbee, a faculty member at Houston Community College in Houston, Texas. The materials used in this textbook/collection were developed by the author and others as independent modules for publication within the Connexions environment. Programming fundamentals are often divided into three college courses: Modular/Structured, Object Oriented and Data Structures. This textbook/collection covers the first of those three courses. The learning modules of this textbook/collection were written as standalone modules. Students using a collection of modules as a textbook will usually view it contents by reading the modules sequentially as presented by the author of the collection. The learning modules of this textbook/collection were, for the most part, written without consideration of a speci??c programming language. In many cases the C++ language is discussed as part of the explanation of the concept. Often the examples used for C++ are exactly the same for the Java programming language. However, some modules were written speci??cally for the C++ programming language. This could not beavoided as the C++ language is used in conjunction with this textbook/collection by the author in teaching college courses.
1. Introduction to Programming -- 2. Program Planning & Design -- 3. Data & Operators -- 4. Often Used Data Types -- 5. Integrated Development Environment -- 6. Program Control Functions -- 7. Specific Task Functions -- 8. Standard Libraries -- 9. Character Data, Sizeof, Typedef, Sequence -- 10. Introduction to Structured Programming -- 11. Two Way Selection -- 12. Multiway Selection -- 13. Test After Loops -- 14. Test Before Loops -- 15. Counting Loops -- 16. String Class, Unary Positive and Negative -- 17. Conditional Operator and Recursion -- 18. Introduction to Arrays -- 19. File I/O and Array Functions -- 20. More Array Functions -- 21. More on Typedef -- 22. Pointers -- 23. More Arrays & Compiler Directives -- 24. OOP & HPC
In English.
Description based on online resource
Keywords: Computer Science -- Textbooks; Programming Languages -- Textbooks